International Study on Microcirculatory Shock Occurrence in Acutely Ill Patients*. Issue 1 (January 2015) - Vellinga, Namkje A. R.; Boerma, E. Christiaan; Koopmans, Matty; Donati, Abele; Dubin, Arnaldo; Shapiro, Nathan I.; Pearse, Rupert M.; Machado, Flavia R.; Fries, Michael; Akarsu-Ayazoglu, Tulin; Pranskunas, Andrius; Hollenberg, Steven; et al.
<x xml:space="preserve">Abstract</x> Objectives: Microcirculatory alterations are associated with adverse outcome in subsets of critically ill patients. The prevalence and significance of microcirculatory alterations in the general ICU population are unknown. We studied the prevalence of microcirculatory alterations in a heterogeneous ICU population and its predictive value in an integrative model of macro- and microcirculatory variables. Design: Multicenter observational point prevalence study. Setting: The Microcirculatory Shock Occurrence in Acutely ill Patients study was conducted in 36 ICUs worldwide. Patients: A heterogeneous ICU population consisting of 501 patients. Interventions: None. Measurements and Main Results: Demographic, hemodynamic, and laboratory data were collected in all ICU patients who were 18 years old or older. Sublingual Sidestream Dark Field imaging was performed to determine the prevalence of an abnormal capillary microvascular flow index (< 2.6) and its additional value in predicting hospital mortality. In 501 patients with a median Acute Physiology and Chronic Health Evaluation II score of 15 (10–21), a Sequential Organ Failure Assessment score of 5 (2–8), and a hospital mortality of 28.4%, 17% exhibited an abnormal capillary microvascular flow index. Tachycardia (heart rate > 90 beats/min) (odds ratio, 2.71; 95% CI, 1.67–4.39; p < 0.001), mean arterial pressure (odds ratio, 0.979; 95% CI, 0.963–0.996; p = 0.013), vasopressor use (odds ratio, 1.84; 95% CI, 1.11–3.07; p = 0.019), and lactate level more than 1.5 mEq/L (odds ratio, 2.15; 95% CI, 1.28–3.62; p = 0.004) were independent risk factors for hospital mortality, but not abnormal microvascular flow index. In reference to microvascular flow index, a significant interaction was observed with tachycardia. In patients with tachycardia, the presence of an abnormal microvascular flow index was an independent, additive predictor for in-hospital mortality (odds ratio, 3.24; 95% CI, 1.30–8.06; p = 0.011). This was not true for nontachycardic patients nor for the total group of patients. Conclusions: In a heterogeneous ICU population, an abnormal microvascular flow index was present in 17% of patients. This was not associated with mortality. However, in patients with tachycardia, an abnormal microvascular flow index was independently associated with an increased risk of hospital death.